2003
DOI: 10.1073/pnas.2534493100
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the substrate-docking site of protein tyrosine kinase C-terminal Src kinase

Abstract: Protein tyrosine kinases (PTK) are key enzymes of mammalian signal transduction. For the fidelity of signal transduction, each PTK phosphorylates only one or a few proteins on specific Tyr residues. Substrate specificity is thought to be mediated by PTKsubstrate docking interactions and recognition of the phosphorylation site sequence by the kinase active site. However, a substratedocking site has not been determined on any PTK. C-terminal Src kinase (Csk) is a PTK that specifically phosphorylates Src family k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
99
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 41 publications
5
99
0
Order By: Relevance
“…For quantifying PTK activities, we measured the phosphorylation of polyE 4Y by using the acid precipitation assay (36). Standard assay reactions of 50 L contained 75 mM 4-(2-Hydroxyethyl)-1-piperazinepropanesulfonic acid (EPPS) (pH 8.0), 1 mg⅐mL Ϫ1 polyE4Y, 200 M [ 32 ]ATP (Ϸ1,000 dpm/pmol), 12 mM MgCl 2, 5% glycerol, and 0.005% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…For quantifying PTK activities, we measured the phosphorylation of polyE 4Y by using the acid precipitation assay (36). Standard assay reactions of 50 L contained 75 mM 4-(2-Hydroxyethyl)-1-piperazinepropanesulfonic acid (EPPS) (pH 8.0), 1 mg⅐mL Ϫ1 polyE4Y, 200 M [ 32 ]ATP (Ϸ1,000 dpm/pmol), 12 mM MgCl 2, 5% glycerol, and 0.005% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…The PS1/c-secretase system regulates Src-Csk association Csk kinase binds Src kinase, decreasing both phosphorylation of Src residue tyr418 and Src activity (Lee et al, 2003). Since the PS1/g-secretase system stimulates phosphorylation of Src tyr418, we asked whether this system affects the Src-Csk association.…”
Section: Ephrinb Ligands Are Cleaved By Mp and Ps1/c-secretasementioning
confidence: 99%
“…Several side chains located in helix D outside the active site of Csk in a docking groove are important in maintaining efficient Src phosphorylation kinetics (19). In a previous study we showed that Csk does not bind with high affinity to Src based on equilibrium sedimentation and single turnover experiments (21).…”
mentioning
confidence: 99%
“…Mutagenesis studies have shown that Csk recognizes not only residues directly in the C terminus but also residues in the large lobe of the kinase domain of Src (17)(18)(19)(20). Several side chains located in helix D outside the active site of Csk in a docking groove are important in maintaining efficient Src phosphorylation kinetics (19).…”
mentioning
confidence: 99%